The Trajectory towards Marginality: How do Older Australians find themselves Dependent on the Private Rental Market?. Issue 1 (2nd August 2012) - Morris, Alan
Abstract : For older Australians being dependent on the private rental market is usually associated with serious financial hardship and insecurity. The article examines the housing careers of older Australians who are dependent on the private rental market. After sketching the policy context, it uses in-depth interviews and a biographical approach to explore their trajectory into the private rental market. Divorce, separation and widowhood were key factors, especially for women, as were poor employment histories and ill-health. The crucial factor was an inability to access social housing. The neglect of this housing tenure has meant that supply is very limited and it is reserved primarily for people with complex needs.